Comparison of spheno-occipital synchondrosis maturation stages with three-dimensional assessment of mandibular growth - Waseem S. Al-Gumaei; Reem Al-Attab; Barakat Al-Tayar; Saba A. Al-hadad; Enas S. Alyafrusee; Abeer A. Al-mashraqi; Najah Alhashimi; Yan Zheng; Maged S. Alhammadi (BMC Oral Health, 2022)
Abstract Background This study aimed to compare spheno-occipital synchondrosis (SOS) maturation stages with a three-dimensional assessment of mandibular growth. Methods This is a cross-sectional study of a retrospective type, in which cone-beam computed tomography (CBCT) images of 500 patients aged 6 to 25 years (226 males and 274 females) were analyzed. The SOS was evaluated using the four-stage scoring system; completely open, partially fused, semi-fused, or completely fused. The SOS scoring and three-dimensional cephalometric measurements were analyzed by Invivo 6.0.3 software. Descriptive and analytical statistics were performed, and a P-value < 0.05 was considered statistically significant. Results There was a statistically significant difference in mandibular measurements among SOS maturation stages in both sexes (P < 0.05). The skeletal growth increments of mandibular variables across the SOS stages had higher mean differences between SOS stages 2 and 3 than those between stages 1 and 2 and stages 3 and 4 in both sexes. The mandibular growth curves increased with chronological age (earlier in females) and SOS maturation stages (mostly in stages 1, 2, and 3 than stage 4). Conclusions The SOS maturation stages are valid and reliable mandibular skeletal indicators as evaluated with three-dimensional cephalometric mandibular measurements. The findings of growth increments and constructed growth curves of mandibular growth might be helpful in diagnosis and treatment planning.